Asuhan Keperawatan Pada Tn. N Dengan Gangguan Sistem Perkemihan: Gagal Ginjal Kronik Di Ruang Anggrek Bugenvil RSUD Pandan Arang Boyolali - MUSTIKA RATRI, ANGGI, Agus Sudaryanto, S.Kep., Ns., M.Kes (2015)
Background: Globally chronic kidney disease caused the death of about 850,000 inhabitants annually, while Indonesia in 2006 reached 100,000 people with chronic kidney disease, and in Boyolali district, especially in RSUD.Pandanarang has reached 8 cases in the last three months. Of the various causes that can lead to chronic kidney disease will cause some complications, therefore chronic kidney disease requires serious treatment so that nurses have to perform nursing care in patients with chronic kidney disease. Objective: To determine the nursing care in patients with chronic renal failure include assessment, intervention, implementation and evaluation of nursing. Methods: The method used is to make the process of nursing care in patients with chronic kidney disease include assessment, intervention, implementation and evaluation of nursing. Results: After nursing actions during 3x24 hours on clients with chronic renal function impairment, the result is reduced client shortness of breath, excess fluid volume is reduced and itching are perceived client is also reduced. Conclusion: In doing nursing care, cooperation among the health care team and the patient's family have been done with optimal but the results could not fit the expected maximum because the client already in stage four.